1996
DOI: 10.1002/bbpc.19961000712
|View full text |Cite
|
Sign up to set email alerts
|

Methylviologen redox reactions at semiconductor single crystal electrodes

Abstract: The mechanism of the two‐step reduction of the methylviologen cation radical (MV2+) was studied at CdS, GaAs and InP single crystal electrodes. In aqueous solution the second step (MV+• → MV0) gives rise to layer formation which is not observed in mixed ethanol/water solutions. This layer has interesting electrical properties. The reoxidation of MV0 occurs by electron injection into the conduction band of all three semiconductors. The reoxidation of MV+• at InP is also a conduction band reaction and electrolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Electron Capture: n-GaAs/MV 2+ . As reported by Schoenmakers et al, methylviologen, dissolved as MV 2+ , is reduced by electron capture at the n-CdS electrode. Furthermore, these authors showed that in a H 2 O−C 2 H 5 OH (1:1) mixture, the final reaction product MV 0 is not absorbed at the CdS surface, in contrast to the behavior in aqueous solutions.…”
Section: Resultsmentioning
confidence: 51%
“…Electron Capture: n-GaAs/MV 2+ . As reported by Schoenmakers et al, methylviologen, dissolved as MV 2+ , is reduced by electron capture at the n-CdS electrode. Furthermore, these authors showed that in a H 2 O−C 2 H 5 OH (1:1) mixture, the final reaction product MV 0 is not absorbed at the CdS surface, in contrast to the behavior in aqueous solutions.…”
Section: Resultsmentioning
confidence: 51%
“…The MV 2ϩ /MV •ϩ /MV 0 reduction and oxidation kinetics have been studied on single crystalline CdS and Si electrodes, and in porous Si. 21,22 The MV 2ϩ /MV oϩ couple has a redox potential of Ϫ0.69 V vs. SCE. 23 The MV •ϩ radical cation, which is formed upon reduction of MV 2ϩ can be further reduced to MV 0 ; redox potentials of Ϫ1.1 to Ϫ1.3 V are reported for the MV •ϩ /MV 0 couple.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that part of the MV 0 layer is removed in the dark. Chemical dissolution of MV 0 is known to occur in aqueous solutions, very likely due to a conproportionation reaction 21 MV 0 (s) ϩ MV 2ϩ r 2MV ϩ…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the approximate photovoltage in Figure 6 is less than the maximum photovoltage attainable with crystalline GaP, even though the valence band edge is approximately 1.5 V more positive than the standard potential for MV 2+/+ . 45,52 Finally, the apparent shapes (i.e., "fill factors") of the photoresponses in Figure 6 were not purely rectangular. These cumulative observations are consistent with material electronic properties (e.g., mobility of the minority carrier) that could stand further improvement.…”
Section: ■ Discussionmentioning
confidence: 98%